Spontaneous remission of advanced progressive poorly differentiated non-small cell lung cancer: a case report and review of literature - Hee-Young Yoon (BMC Pulmonary Medicine, 2019)
Abstract Background Spontaneous remission (SR) of cancer is a very rare phenomenon of unknown mechanism. In particular, SR of non-small cell lung cancer (NSCLC) has been scarcely reported. We present the case of a 74-year-old woman with advanced, poorly differentiated NSCLC (highly expressing programmed death ligand-1 [PD-L1]) that progressed despite multiple lines of chemotherapy but then spontaneously remitted. CASE presentation The patient presented with hemoptysis and was diagnosed with stage IIIA poorly differentiated NSCLC via bronchoscopic biopsy. She had an unremarkable medical history and moderate performance status. The initial treatment plan was surgery after neoadjuvant chemotherapy. Despite conventional chemotherapy, follow-up chest computed tomography (CT) showed gradual tumor progression and she decided against further treatment after fifth-line chemotherapy. However, the size of lung mass was markedly decreased on follow-up chest CT one year after ceasing chemotherapy. Also, follow-up positron emission tomography images showed decreased metabolic activity in the lung mass and a percutaneous biopsy specimen from the diminished lung mass revealed no viable tumor cells. A diagnosis of SR of NSCLC was confirmed, and the patient was without tumor progression on follow-up nine months later. Later, PD-L1 immunostaining revealed high positivity (> 99%) in initial tumor cells. Conclusion Our case showing SR of poorly advanced NSCLC refractory to multiple lines of chemotherapy suggested the association between immunity and tumor regression.